MuStServ: A Lightweight Multimedia Streaming Server - Sulaiman, Ahmad Suhaily (Universiti Teknologi Petronas, 2006)
Media streaming is no longer a new term, more so after broadband internet connection became more of a necessity than luxury in most homes. The objective of this project is to come up with a streaming solution for multimedia files that utilizes as little system resources as possible and is not platform-dependent. To tackle this project, I followed a series of steps; namely research, designing the system architecture, develop the system, and test it. Python, JAVA, and PERL were analyzed to determine which programming language is the most suitable to be used. Those steps were then succeeded by choosing what transfer mode to be employed. As a result of the analysis, Python was decided the most suitable programming language to be used because it is easy to learn and fast to develop. HTTP streaming was the transfer mode of choice simply because it is easier to implement compared to UDP. Tests showed that MuStServ consumes significantly lower memory compared to Apache, the most widely used and easiest way to implement HTTP streamer. Thus, it can safely be concluded that this project has achieved its goal. The usage of efficient programming language, good architecture and also sheer simplicity in its design are the secrets why MuStServ is so lightweight.